Global Santri Narratives: A Study of English Language Products at Al-Yasini Islamic Boarding School as a Cultural Strategy for Students in an Automated World Ecosystem - Dewi Masita; Wilda Rihlasyita (Schemata: Jurnal Pascasarjana UIN Mataram, 2025)
Amidst the rapid flow of globalization and digital transformation marked by the presence of machines, robots, and artificial intelligence, the cultural identity of Islamic boarding schools faces new challenges. This research is significant because it examines how Generation Z students at Al-Yasini Islamic Boarding School adapt to the automated world through linguistic strategies, particularly in their use of English as a symbol and tool of distinction. This research aims to understand the practices and meanings behind the linguistic products produced by students in a modern context, and how this process shapes their identity and social position in global society. This research employs a qualitative approach, utilizing case studies and in-depth interviews with students from the Foreign Language Development Institute, language dormitory mentors, and English teachers. Two theories are used to interpret this phenomenon: Pierre Bourdieu's Cultural Capital, which explains how language becomes a form of symbolic capital in the social structure of Islamic boarding schools, and Jan Nederveen Pieterse's Cultural Hybridization, which highlights how local Islamic boarding school values are reformulated into a global format through English narratives. The results show that Islamic boarding school students not only master language as a technical skill but also produce cultural artifacts such as poetry, speeches, and books in English that combine Islamic values with global expressions. The main findings demonstrate the transformation of the students' identities from local actors to global students capable of negotiating their position in the posthuman world order. The novelty of this research lies in the discovery that Islamic boarding schools, as traditional institutions, can create a foreign language-based educational model that is not assimilative, but rather hybrid, blending local values and global strategies. The theoretical implications enrich the discourse on Islamic boarding school education as a space for the production of cultural capital and a dynamic and reflective field of cultural hybridization towards the future